ANALISIS PENGEMBANGAN SUMBER DAYA MANUSIA DALAM PENINGKATAN KINERJA ANGGOTA - Abbas Abbas; Elyasyah Putra (e-JKPP, 2019)
Elansyah Putra, Analysis of Human Resource Development in Improving Members' Performance (Case Study in the Way Way Resort Police).The problems in this study are (1) How is the development of human resources for members of the Way Kanan Police Department through education and training in realizing the professionalism of the Indonesian National Police? (2) What aspects support and hinder the development of human resources for members of the Way Kanan District Police?The method used in this study is the ethnographic research method. Ethnographic research methods are included in qualitative research methods. The word ethnography comes from the Greek words ethos which means ethnicity and graphos which means something written, ethnography is the science of writing about ethnic groups, using more contemporary language, ethnography is an in-depth study of natural behavior in a culture or an entire social group.The results showed that the development of human resources in the members of the Way Kanan Resort Police, through (1) Education, in general members of the Way Kanan Resort Police still have high school education, (2) Training, has been carried out but not all members of the police follow regularly, ( 3) Skills, in general, members of the Way Kanan Police Department have good work skills, although not yet optimal because the level of education and training also has a contribution to skilAspects that hinder the development of Human Resources in Improving the Performance of Members of the Way Kanan Police Department, that is, not all members have good knowledge of the rules system and compliance with the organizational rules system. The main weakness in developing human resources is due to the lack of opportunities and the absence of opportunities for members to develop their abilities through formal education, training and the lack of work facilities and infrastructure, so that the development of human resources is not optimal. While the supporting aspect is the opportunity given by the leadership to attend higher level formal education